Related-party transactions and financial statement comparability: evidence from South Korea. Issue 2 (2nd April 2016) - Lee, Myung-Gun; Kang, Minjung; Lee, Ho-Young; Park, Jong Chool
Abstract : This study examines the association between related-party transactions (RPTs, hereafter) and comparability of accounting information. We posit that comparability decreases with RPTs where much management discretion is likely to be involved in determining volume and terms. In addition, firms conducting RPTs are more likely to make accounting choices which make their accounting information less comparable to their industry peers to prevent government detection of illegal RPTs. Using a unique data-set on RPTs among firms listed on the Korean stock market, we provide evidence consistent with our prediction. Specifically, by defining three different measures of annual RPTs; (1) size of RPTs, (2) volatility of RPTs, and (3) size of non-cash RPTs, we find that financial statement comparability decreases as RPTs increase for all three measures of RPTs. Additional analyses show that the negative association is more pronounced in abnormal RPTs than the predicted RPTs and less pronounced in operating RPTs than non-operating RPTs.